The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.37934/cfdl.13.4.1137
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characteristics of Disk Bypass Pipeline Inspection Gauge (PIG) in Natural Gas Pipelines using Computational Fluid Dynamics

Abstract: Disk bypass pipeline inspection gauge (PIG) is considered as an efficient device for pigging operations including cleaning, maintaining and inspecting pipelines. The PIG performance is influenced by the fluid flow characteristics as PIG moves forward due to differential pressure of fluid around the PIG. This study focuses on flow characterization of fluid around disk bypass PIG for natural gases pipelines including methane, ethane, and butane using computational fluid dynamics approach. The control volume meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…where, ks is the thermal conductivity of the solid material. The effect of turbulent fluctuations was modelled using standarded k- model [26], and the near-wall regions were treated using the standard wall function.…”
Section: Conservation Of Energymentioning
confidence: 99%
“…where, ks is the thermal conductivity of the solid material. The effect of turbulent fluctuations was modelled using standarded k- model [26], and the near-wall regions were treated using the standard wall function.…”
Section: Conservation Of Energymentioning
confidence: 99%
“…Alternatively, complex and costly solid oxide fuel cell experiments require dynamic computational fluid simulations. CFDs have been used in many studies; for example, an overview of computational fluid dynamics modelling in solid oxide fuel cells has been presented in [19], and it has been shown that it is easier to see the flow of natural gas pipelines that are difficult to access through use of CFDs [22]. Fluid aerodynamics have been simulated to visualize the performance of various NACA airfoils [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, this first law-based energy analysis cannot provide the actual losses of the system in terms of efficiency and thermodynamic losses [1,[8][9][10][11][12][13][14][15][16][17][18]. Therefore, it is important that the energy conversion efficiency of a system be analyzed by considering both the first and second laws of thermodynamics [19][20][21][22][23][24]. Second law-based exergy analysis provides a better view of the energy losses to the environment and the process-related internal irreversibility.…”
Section: Introductionmentioning
confidence: 99%